ADOLESCENT PHENOMENONS THAT WORK AS FEMALE SEX WORKERS IN KUPANG CITY ON MAY - OCTOBER 2019 - Luisa Octoviana Eluama; Wahyul Anis; Nining Febryana (UNIVERSITAS AIRLANGGA, 2020)
ABSTRACT Background : The problem of adolescence becoming sex workers in Indonesia is still high. Tanpa Batas Foundation in Kupang City on May-October 2017 shows adolescence as women who have sex workers that identified almost all aged 13-24 years of 190 cases. Meanwhile, there are many unidentified practices of prostitution like an iceberg phenomenon. This study aimed to identified the level of education, income, knowledge, perception, the reason, experience, the effect of social media and expectations that affects adolescence becoming sex workers. Method : Qualitative study with a phenomenological approach. Determination of respondents conducted with non-probability sampling techniques used purposive sampling and obtained respondents as much as 10 adolescence of sex workers. The collected data used indepth interview guidelines with semi structured questions. Instruments of this study were transcripts, notebooks, questionnaire and cameras for documentation. Data analysis was starting with the transcript of data, by analyzing the words from the respondent, finding the keyword, making the category followed by identifying the theme and interpretation into a descriptive. Result : This study showed the level of education respondents started from : not went to school, junior high school, senior high school with monthly average income of 1-2 million. Most of the respondents have a bad preception of their self, economic problems were still the main reason and facebook was the most effect from social media to women’s sex worker, in addition to the results of knowledge level showed that all respondents have a good knowledge, they also hope could find another job better and decent. Conclusion : Economic insistence, the adverse effect of social media and peers became the main cause of adolescence become sex workers despite having a good knowledge and they also had the hope that could stop and exit of the employment as a sex workers by finding a better job and feasible of the norm and culture of society.